Factors determining the performance of indexing systems. Volume 1, Design, Pt 2, Appendices - Cleverdon, Cyril W.; Mills, Jack; Keen, Michael (Cranfield University, 1966)
The appendices which follow provide complete information concerning the collection of documents and the set of questions used in the investigation, and are included with the intention that it should be possible for anyone - if they should wish to do so - to repeat the test.